PERFORMANCE MONITORING ALGORITHM FOR OPTIMIZING ELECTRICAL POWER GENERATED BY USING PHOTOVOLTAIC SYSTEMS - VIJAYA KUMAR, PRADEEP MENON (2023)
Power generation by harnessing the energy received from sunlight is a fast-growing industry that despite its benefits in terms of sustainability, is plagued with issues that very often go unnoticed and subsequently unattended to. Given the vast area needed to generate a plausible amount of electricity, it is substantially difficult to trace where the fault has occurred or more importantly what fault is it that is inhibiting the power generation capacity. The main aim of this research work is to develop a suitable performance monitoring and fault detection mechanism that can effectively communicate errors that have taken place to the user. The 5 main faults that were identified for this research are encapsulation failures, module corrosion and hotspots, which are the two most critical faults, and the others were broken interconnections, cell cracking and dust buildup on the surface of the panel.